Respuesta :

3x^2 = 7x - 3
3x^2 - 7x = -3
x^2 - 7/3x = -1
x^2 - 7/3x + 49/36 = -1 + 49/36 = 13/36
(x - 7/6)^2 = 13/36
x - 7/6 = + or - sqrt(13)/6
x = 7/6 + or - sqrt(13)/6
x = (7 + or - sqrt(13))/6

we have

[tex]3x^{2}=7x-3[/tex]

Group terms that contain the same variable, and move the constant to the opposite side of the equation

[tex]3x^{2}-7x=-3[/tex]

Factor the leading coefficient

[tex]3(x^{2}-(7/3)x)=-3[/tex]

Complete the square. Remember to balance the equation by adding the same constants to each side

[tex]3(x^{2}-(7/3)x+(49/36))=-3+(49/12)[/tex]

[tex]3(x^{2}-(7/3)x+(49/36))=(13/12)[/tex]

Rewrite as perfect squares

[tex]3(x-(7/6))^{2}=(13/12)[/tex]

[tex](x-(7/6))^{2}=(13/36)[/tex]

square root both sides

[tex]x-\frac{7}{6}=(+/-) \sqrt{\frac{13}{36}}[/tex]

[tex]x-\frac{7}{6}=(+/-) \frac{\sqrt{13}}{6}[/tex]

[tex]x=\frac{7}{6}(+/-) \frac{\sqrt{13}}{6}[/tex]

The solutions are

[tex]x=\frac{7}{6}+\frac{\sqrt{13}}{6}=\frac{-7+\sqrt{13}}{6}[/tex]

[tex]x=\frac{7}{6}-\frac{\sqrt{13}}{6}=\frac{-7-\sqrt{13}}{6}[/tex]

therefore

The answer is

[tex]x=\frac{7\pm\sqrt{13}}{6}[/tex]